Environmental sustainability of food systems, global food security and trade - Glauber, Joseph W.; Laborde Debucquet, David; Piñeiro, Valeria; Elverdin, Pablo; Illescas, Nelson (T20 Indonesia, 2022)
The challenges faced by the global agri-food system are very complex. It must not only provide a sufficient nutritious food supply to meet growing demand, but it also requires managing environmental issues such as the impact of climate change, the pressure on natural resources, and the ecological sustainability of agricultural practices.